2021
DOI: 10.1088/1742-6596/2101/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Design of Low-Pressure Sand Casting Process for Water-Cooled Motor Shell in Electric Vehicle

Abstract: Aluminium alloy motor shell is the core part of the new energy vehicle powertrain. It has a complex structure with an average wall thickness of 4∼5mm, a side wall with 6∼7mm spiral water jacket, and the bottom of the shell inlaid with cast steel bearing bushing. Because of its complex structure characteristics, as well as higher internal quality requirements and air tightness requirements, the casting process of motor housing is very difficult. This paper introduces the structural characteristics and common ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The housing jacket is made of different alloys, and liquid distribution inside the jacket is provided by axial or tangential cooling ducts with rectangular cross-sections [42,[104][105][106]. The most common technology used to manufacture the housings of such motors is casting using aluminum alloys [137]. The design utilizing an axial arrangement of the ducts decreases the motor's temperature, but the load on the circulation pump is greater due to greater hydraulic losses (pressure drop) in the ducts (Figure 7) [35,102,103].…”
Section: Liquid Cooling Systemsmentioning
confidence: 99%
“…The housing jacket is made of different alloys, and liquid distribution inside the jacket is provided by axial or tangential cooling ducts with rectangular cross-sections [42,[104][105][106]. The most common technology used to manufacture the housings of such motors is casting using aluminum alloys [137]. The design utilizing an axial arrangement of the ducts decreases the motor's temperature, but the load on the circulation pump is greater due to greater hydraulic losses (pressure drop) in the ducts (Figure 7) [35,102,103].…”
Section: Liquid Cooling Systemsmentioning
confidence: 99%
“…This implementation enables a potential increase in the PDR, reaching levels of 2.5-2.7 kW/kg [10,42]. Recent research has suggested that multi-circuit low-temperature cooling systems are a promising solution to provide reliable and safe operation of electric motors together with the high economic efficiency of the cooling method [44][45][46][47]. Such systems have a simple design of cooling circuits, are reliable, small, have flexibility of operation, a high reduction of stator and rotor temperatures, and good motor performance.…”
mentioning
confidence: 99%